Genomic Analysis of Stress Associated Proteins in Soybean and the Role of GmSAP16 in Abiotic Stress Responses in Arabidopsis and Soybean - Zhang, Xiang-Zhan; Zheng, Wei-Jun; Cao, Xin-You; Cui, Xi-Yan; Zhao, Shu-Ping; Yu, Tai-Fei; Chen, Jun; Zhou, Yong-Bin; Chen, Ming; Chai, Shou-Cheng; Xu, Zhao-Shi; Ma, You-Zhi (Frontiers in Plant Science, 2019)
Stress associated proteins (SAPs) containing A20/AN1 zinc finger domains have emerged as novel regulators of stress responses. In this study, 27 SAP genes were identified in soybean. The phylogenetic relationships, exon-intron structure, domain structure, chromosomal localization, putative cis-acting elements, and expression patterns of SAPs in various tissues under abiotic stresses were analyzed. Among the soybean SAP genes, GmSAP16 was significantly induced by water deficit stress, salt, and abscisic acid (ABA) and selected for further analysis. GmSAP16 was located in the nucleus and cytoplasm. The overexpression of GmSAP16 in Arabidopsis improved drought and salt tolerance at different developmental stages and increased ABA sensitivity, as indicated by delayed seed germination and stomatal closure. The GmSAP16 transgenic Arabidopsis plants had a higher proline content and a lower water loss rate and malondialdehyde (MDA) content than wild type (WT) plants in response to stresses. The overexpression of GmSAP16 in soybean hairy roots enhanced drought and salt tolerance of soybean seedlings, with higher proline and chlorophyll contents and a lower MDA content than WT. RNA inference (RNAi) of GmSAP16 increased stress sensitivity. Stress-related genes, including GmDREB1B;1, GmNCED3, GmRD22, GmDREB2, GmNHX1, and GmSOS1, showed significant expression alterations in GmSAP16-overexpressing and RNAi plants under stress treatments. These results indicate that soybean SAP genes play important roles in abiotic stress responses.